Perforation of the right atrial appendage during implantation of a leadless pacemaker. Issue 1 (29th December 2021) - Date, Kazuma; Murata, Tomohiro; Mano, Akiko; Kawata, Mitsuhiro; Kyo, Shunei
Abstract : We report a case of perforation of the right atrial appendage during implantation of a leadless pacemaker in a 94 years old woman. We performed emergency surgery to repair the perforation site. To our konwledge, there are few reports of right atrial perforation during a leadless pacemaker indwelling.